MUSLIMS AND EUROPE: A DEMOGRAPHIC STUDY OF CITATIONS FROM THE INDEX ISLAMICUS DATABASE - Ali Anwar, Mumtaz (Malaysian Journal of Library and Information Science, 2001)
This study identifies the subject focus and trends in the growth of literature on Muslims after the dissolution of the Soviet Union in late 1991. Index Islamicus on CD-ROM was used as the source for citations on ‘Europe’ and ‘Muslims’ for two 5-year periods, i.e., 1986-90 and 1992-96. A demographic analysis of 277 citations were analysed in terms of periodic growth, subject focus, geographic origins, language of citations, and major authors. The amount of literature increased by 159.7 percent with greater emphasis on many subjects, especially on Muslims in Central Asia, Muslim Minorities, Fundamentalism and Revivalism. The number of journals publishing literature in this area increased from 17 titles in 1986-90 to 64 in 1992-96. The number of authors increased from 66 in 1986-90 to 203 in 1992-96. The study shows various growth trends that have developed during 1992-96 and identifies a drastic shift in focus on various subjects dealing with Muslims.